Rancang Bangun Website Pembelajaran dengan Model Team Games Tournament - Wardana, Aditia; Kuncoro, Adam Prayogo; Suliswaningsih, Suliswaningsih; Wijaya, Anugerah Bagus (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Since the advent of modern communication and information technologies, the field of education and learning has seen profound transformations. Websites that can access different kinds of data online are one example of this. Some schools still haven't figured out how to make the most of the internet, despite the fact that it has revolutionized many parts of life, including education. Colleges and universities must adapt to the changing times by implementing new methods of learning that raise the bar for student achievement. Unfortunately, many teachers still rely on the ineffective lecture format, which results for dull and unengaging classroom discussions. Hence, new approaches to education are required. Learning using the TGT (Team Games Tournament) concept is something to think about. By combining aspects of teamwork and competition, this approach creates engaging and motivating games that promote the application of learning principles. Technology, particularly websites, plays an important role in implementing the TGT paradigm in learning. Applications that facilitate the use of the TGT learning paradigm are the focus of this study. We used the waterfall approach for this study. This allows for the implementation of innovative learning strategies, which in turn boost student engagement and the quality of their learning. By using information technology, this TGT model-based application aims to improve the learning process and address the drawbacks of conventional learning approaches.